197k views
2 votes
Apply all relevant properties of

Apply all relevant properties of-example-1

1 Answer

2 votes

Recall that, when two terms are being multiplied and they have the same number we can add the exponents:


x^nx^m=x^(n+m).

Applying the above property to the given expressions, we get:


\begin{gathered} 6^{(9)/(5)}6^{(1)/(5)}=6^{(9)/(5)+(1)/(5)}, \\ x^{(10)/(3)}x^{(11)/(3)}=x^{(10)/(3)+(11)/(3)}, \\ y^{(7)/(2)}y^{(1)/(2)}=y^{(7)/(2)+(1)/(2)}. \end{gathered}

Simplifying the above results, we get:


\begin{gathered} 6^{(9)/(5)}6^{(1)/(5)}=6^2, \\ x^{(10)/(3)}x^{(11)/(3)}=x^7, \\ y^{(7)/(2)}y^{(1)/(2)}=y^4. \end{gathered}

Answer:


\begin{gathered} 6^{(9)/(5)}6^{(1)/(5)}=6^2, \\ x^{(10)/(3)}x^{(11)/(3)}=x^7, \\ y^{(7)/(2)}y^{(1)/(2)}=y^4. \end{gathered}

User Eich
by
5.3k points